ANALISIS KEBUTUHAN SUMBER DAYA MANUSIA TERHADAP BEBAN KERJA DI BAGIAN REKAM MEDIS MENGGUNAKAN METODE (WORK LOAD INDICATOR STAFFING NEED) DI RUMAH SAKIT UMUM PERMATABUNDA MEDAN TAHUN 2019 - Puput Melati Hutauruk; Meha Marito Br Gurning (Akademi Perekam dan Informasi Kesehatan Imelda, 2020)
Human Resources (HR) is needed so that the availability of qualified medical personnel and in accordance with the needs of medical personnel needed to ensure the implementation of health development in order to improve the highest degree of public health. The purpose of this research is to know the planning of human resources (HR) needs of the medical record unit at the Medan Permata Bunda Hospital This type of research is descriptive. The method used in this study is the method of observation and interviews. The population in this study was a medical record unit of 9 people. Samples were taken by total sampling. Available working time based on the amount of effective work totaling 2475 / year, in 1 effective working day is 7 hours. The number of outpatient visits was 43669 patients / year, while the number of inpatient visits was 9284 patients / year. The standard time allowance for officers is 0.01 minutes. Based on the calculation of workforce requirements using the WISN formula that has been carried out in the medical record unit of the Permata Bunda General Hospital in Medan, there were 13 officers, and the number of officers in the medical record unit was 9 people. It is recommended to Permata Bunda General Hospital to add 4 medical record officers with D3 Medical Record education qualifications.